DEVELOPING A MULTIFUNCTIONAL BALL FOR TEACHING PHYSICAL EDUCATION, SPORT AND HEALTH - Hartono, Mugiyo; Rahayu, Setya (The Journal of Educational Development, 2016)
Students understand and develop movement skills through various sport games, but they have less enjoyable experience because of inappropriate and uncomfortable ball size. The existing standard balls often frighten the students because of their weight and may hurt them when the balls hit their body parts. This study is intended to design a multifunctional ball for basket ball, volley ball and football and to find out how it can improve the students’ motivation in the teaching of Physical Education, Sport and Health in Primary and Junior High Schools in Semarang. This is a research and development study. The sample of 36 students were selected for the small-scale testing and 72 students for the large-scale testing. The results of the study show that the final product was a multifunctional ball with the size of 66 cm, made of soft, unslippery Poly Urhetane sponge, 270 gram in weight, air pressre of 0.250-0.3 bar and the bounce of 105-115. The ball was designed in light and interesting color. The final product has two functions for basket ball, volley ball and football, and does not cause pain because of their light in weight and reasonable size.